Accurate determination of low-level chemical oxygen demand using a multistep chemical oxidation digestion process for treating drinking water samples. Issue 18 (27th April 2016) - Ma, Yongjun; Tie, Zhenzhen; Zhou, Min; Wang, Na; Cao, Xiaojuan; Xie, Yun
Abstract : A multistep wet-chemical oxidation digestion technique was developed for determination of low-level COD in drinking water by using a potentiometric titration method. Abstract : An improved automatic potentiometric titration method for the determination of the low-level chemical oxygen demand (COD) in drinking water was proposed and validated. In this method, a special digestion procedure that combines the advantages of both alkaline potassium permanganate and acidic potassium dichromate digestion mode was adopted. Under optimized operation conditions, the proposed method was successfully applied to determine the COD values of tap water and marketable bottled water samples with satisfactory results. Specifically, the tolerable interference concentration of chloride ions for a drinking sample was confirmed to be up to the level of 90 mg L −1 . Thus, for measuring the low-level COD values of drinking water, the new method offered several technical characteristics that include high degradation efficiency, good precision, less sampling volume (only 10.00 mL), short analysis time (about 25 min required per sample), use of the mercury-free catalysts, a low detection limit (0.11 mg O2 L −1 ) and a broad linear range of COD values (0.2–25.0 mg O2 L −1 ).